Meningkatkan Gaya Hidup Sehat Pekerja Melalui Spiritualitas dan Kohesivitas Keluarga - Shafa Safira Aulia Putri; Althriyani; Melok Roro Kinanthi; Febriani, Zulfa (Lembaga Penelitian Universitas YARSI, 2024)
Non-communicable diseases are emerging among the working-age population in Jakarta during early productive years. This trend may be attributed to a lack of attention to healthy lifestyles and the dynamics of social relationships. This study aimed to determine the significant roles of spirituality and family cohesiveness in the dimensions of a healthy lifestyle, including nutrition, physical activity, stress management, spiritual growth, interpersonal relationships, and health responsibility. The research was correlational in design, with a sample of 195 workers in Jakarta (M = 26.29 years) recruited through convenience sampling. Data were collected using the Health Promoting Lifestyle Profile-II, the Brief Measurement of Religiosity-Spirituality Scale, and the Brief Family Relationship Scale, and were analyzed using multiple regression techniques. The results showed that, simultaneously, spirituality and family cohesiveness significantly contributed to spiritual growth (R2 = 29%; F (2,192) = 39,152; p < ,001), interpersonal relationship (R2 = 26,3%; F (2,192) = 34,183; p < ,001), dimensi stress management (R2 = 16,7%; F (2,192) = 19,194; p < ,05), dan nutrition (R2 = 4,6%; F (2,192) = 4,645; p < ,05). These findings suggest that promoting healthy lifestyles among workers in Jakarta may benefit from an approach that integrates spirituality and family cohesiveness values